Collision severity evaluation of unmanned aerial vehicles (UAVs) impacting on aircraft structures - Kumar, Sivakumar Anush (Nanyang Technological University, 2021)
This paper is devoted to investigating the collision severity of generalized UAVs impacting aircraft engines. The peak impact force and fracture of the CFM56 engine blades were evaluated using FEM and Explicit Dynamics simulations on ABAQUS. In this study, Multiple Linear Regression (MLR) analysis was performed to obtain appropriate dimensions for the modelling of quadcopter UAVs. Maximum Take-off Mass (MTOM) values of 0.5kg, 1kg, 2kg were assigned based on dimensional analyses from 39 commercial UAVs. For the simulation, parametric variations in MTOM, aircraft speed of UAV, and rotational speed of engine fan blades were adopted. Results indicated that contact forces to the blades due to collision were more severe with UAV MTOM of 1 kg and above. This was prominent in the most severe case, with the UAV camera having a head-on collision with a fan blade. However, it was notable that simulations were case-dependent as the UAV trajectory and point of collision varies for each scenario. Further studies are required to consider the influence of various UAV trajectories and component level sizing on the engine collision severity.